2019
DOI: 10.1016/j.sjbs.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotic resistant mastitis pathogens in dairy cows in Egypt and potential biological control agents produced from plant endophytic actinobacteria

Abstract: Dairy production is threatened by antibiotic resistant pathogens worldwide, and alternative solutions to treat mastitis are not available. The prevalence of antibiotic resistant strains is not well known in less developed countries. The prevalence of pathogenic bacteria and their resistance to 21 commercial antibiotics were studied in milk samples taken from 122 dairy cows suffering from the symptoms of mastitis in Egypt. The bacterial species were identified with molecular methods, and antibiotic resistance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
2
25
0
6
Order By: Relevance
“…Methicillin-resistant S. aureus (MRSA) strains can cause nosocomial infections and consequently high mortality in humans [3]. In Egypt, there was high prevalence of resistance among S. aureus in bovine species to antimicrobial agents such as β-lactams, which are used to treat mastitis [4,5]. This high prevalence is caused by the uncontrolled widespread use of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant S. aureus (MRSA) strains can cause nosocomial infections and consequently high mortality in humans [3]. In Egypt, there was high prevalence of resistance among S. aureus in bovine species to antimicrobial agents such as β-lactams, which are used to treat mastitis [4,5]. This high prevalence is caused by the uncontrolled widespread use of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ESBL producers are described infrequently in E. coli isolated from bovine mastitis in Germany, France, Switzerland, and the UK [29][30][31][32]. The susceptibility of E. coli strains isolated from milk samples is also documented by Hinthong et al [18] and Ameen et al [33]. The majority (68%) of the E. coli isolates from cows with mastitis in Switzerland were fully susceptible to all antimicrobials tested.…”
Section: Discussionmentioning
confidence: 67%
“…Multidrug resistance was observed in 38.4% of isolates (Tahar et al, 2020). In a similar study in Egypt (Ameen et al, 2019), the E. coli strains isolated from cow milk were resistant to AM (33%), SXT (23%), and TET (16%) or AMC (6.6%). In Switzerland (Nüesch-Inderbinen et al, 2019), the E. coli strains isolated from cow milk were resistant to AM (22%), TET (16%), SXT (9.8%), gentamicin (3.7%), or to AMC (2.4%).…”
Section: Discussionmentioning
confidence: 78%
“…When this prevalence was compared with the prevalence of other studies of the literature, the present prevalence is high. For instance, a prevalence of 6.5% was found in Jordan (Ismail andAbutarbush, 2020), 10% in Mexico (Olivares-Pérez et al, 2015), 11.1% in China , 15.5% in Belgium (Verbeke et al, 2014) and 7% in Egypt (Ameen et al, 2019). Interestingly, the present E. coli prevalence in the current study was approximately close to the prevalence (26%) found in another recent study in Algeria (Tahar et al, 2020) or a study in Ethiopia (27.3%) (Haftu et al, 2012), and lower than the prevalence found in Tunisia (31.7%) (Saidani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%